(untitled) (Gaceta Técnica, 2023)
The editorial committee of the Gaceta Técnica journal, through this editorial, presents posthumous tribute to an outstanding person, who participated as the author of articles for this scientific publication, as well as an expert content evaluator for it. Civil Engineer graduated from the Lisandro Alvarado Centroccidental University (UCLA), and later accepted as a teacher in the same institution, died on July 5 of this year, in Barquisimeto city , Dr. María Ysabel Dikdan Jaua; his loss being unfortunate because his life and work transcended not only in Venezuela, but also in other borders.